Improving Quality of Health Service Through Accreditation - Mey Lona Verawaty Zendrato (Journal of Global Research in Public Health, 2022)
Every citizen has the right to get comprehensive health services, but the current condition is that there are many complaints and dissatisfaction with health workers and health facilities. The purpose of writing this article is to provide an overview of the importance of creating quality health services through increasing accreditation culture. The method used through literature review. It was found from the results of the study of this article that the implementation of accreditation has not been cultured optimally, this is because some views of the accreditation process are momentum and technical in nature. Therefore this view must be changed, through improvements from various aspects. Things that can be done such as change together, commitment, creating a service focus on patient health and safety, and creating healthy hospital management.